Risk of Hemodynamic Disorder in Cats in Surabaya and Surrounding Areas with Erythrocyte and Platelet Components Analysis - Kurnia Desiandura; Indra Rahmawati; Rondius Solfaine (Wikrama Parahita : Jurnal Pengabdian Masyarakat, 2025)
The community service program by lecturers of the Faculty of Veterinary Medicine, University of Wijaya Kusuma Surabaya, in collaboration with WEKA Veterinary Teaching Hospital. Many cat owners are unaware of the clinical symptoms of hemodynamic disorders, such as fatigue, weakness, tiredness, lethargy, or even a decreased or loss of appetite. However, visible clinical signs, such as pale gums or mucous membranes, and shortness of breath, sometimes prompt cat owners to consider what to do. This program aims to educate the public regarding the risk factors for hemodynamic disorders that affect the general condition of the cats with blood tests for erythrocyte and platelet components. This program focuses on cats cared for by owners in Surabaya and its surroundings. The method for identifying risks of hemodynamic disorder is a blood test with a hematology analyzer, and it is free of charge. The contribution of this activity is Improvement awareness and knowledge of pet owners, especially cat's owners, about the importance of blood tests to reduce the risk factors for hemodynamic disorders in cat health. This activity uses sample of 25 cats from 25 different owners, which were taken randomly without looking at clinical symptoms. Blood samples were taken and continued with the Raito-vet® hematology analyzer to determine the components of the erythrocyte and platelet values. The results showed that all samples had anemia, and 19 cats had thrombocytosis. After the results were obtained, a discussion and education stage was carried out with cat owners regarding the condition and further treatment of the cat. Cats without significant symptoms can experience hemodynamic disorders, as evidenced by the fact that almost all cats participating in this program had abnormal erythrocyte and platelet counts. A blood test with a hematology analyzer is an effective supporting diagnosis for detecting hemodynamic disorders or blood abnormalities in cats. Therefore, the results of this test play a significant role in ensuring cat owners are more aware and vigilant about the effects of abnormal blood results and in deciding on further action to improve their cat's health. This program also helps veterinarians provide education and advice to cat owners so they can pay more attention to their cat's health through various stages of prevention and treatment, so that diseases can be detected early, are not fatal, and improve cat health.